Physical and Microbiological Qualities of Kampong-Broiler Crossbred Chickens Meat Raised in Different Stocking Densities - C. A. Patria; R. Afnan; I. I. Arief (Media Peternakan, 2016)
The crossbreeding between broiler and kampong chickens has been performed to develop a kampong-broiler strain chicken. The chicken stocking condition needs more attention as a part of animal welfare. This study was performed to identify the relationship between the stocking density and the stress based on Temperature Humidity Index (THI) and the effect of stocking density on meat quality, i.e., physical, microbiological, and organoleptic. Ninety DOCs of Kampong-Broiler (KB) were assigned into a completely randomized design with 3 treatments of stocking density  i.e., 8, 10, and 12 birds m-2. Each treatment was replicated 3 times. The experimental chickens were housed in 9 blocks of housing each with 1 x 1 m2 size. Data on physical and microbiology of meat qualities were analyzed with analysis of variance and continued with Duncan’s multiple range test. The organoleptic data were analyzed by using Kruskal-Wallis test. The result showed that the stocking density did not significantly affect the physical and hedonic quality of KB chicken’s breast. The stocking densities significantly affected (P<0.05) the microbiological variables of breast meat. The average value of THI during maintenance reached 28.98±1.25–29.33±1.32oC. The higher the animal density the higher the THI value that correlated to the stress condition. However, high stocking density did not affect the physical and hedonic quality of breast meat,  thus it can be accepted by the consumers. The higher the stocking density the higher the total plate count, Escherichia coli, and Staphylococcus aureus, without the presence of Salmonella sp. The meat quality of KB chickens raised in the stocking density of 10 birds m-2 meets the requirement of SNI 01-3924-2009.